Does individual adaptability mediate the relationship between personal initiative and psychological well-being: evidence from Uganda’s small enterprises - Tabala, Agnes; Munene, John; Kagaari, James; Mafabi, Samuel; Kyogabiirwe, Jannat (Emerald, 2024)
Purpose – This paper aims to investigate whether individual adaptability mediates the relationship between personal initiative (PI) and psychological well-being of Ugandan small enterprise employees. Furthermore, the paper examines whether PI and individual adaptability also affect psychological well-being. Design/methodology/approach – A cross-sectional survey design using quantitative approach was used in this study. Data were collected from 726 employees of small enterprises in Uganda using a self-administered questionnaire. Data were analyzed using the Statistical Package for Social Scientists and uploaded into AMOS version 23. Hypotheses were tested using structural equation modeling technique. Findings – Results confirm that individual adaptability fully mediates the relationship between PI and psychological well-being. Findings further indicate that PI is negatively related to psychological well-being and that individual adaptability is positively related to psychological well-being. Research limitations/implications – First, the sample of this study consisted of employees working with small enterprises in Uganda with different demographic characteristics; thus, the generalizability of these findings to other sectors or contexts needs to be established. Secondly, the study was quantitative in nature. This study has managerial implications in a way that managers need to create a climate that fosters individual adaptability among employees to help them enhance their Psychological well-being (PWB). Practical implications – Small enterprise employees with high levels of PI may benchmark on this study findings by ensuring that they adjust their thinking, emotions and behavior to navigate the challenges of the current working environment such that they can increase their psychological well-being Originality/value – This study may be among the first to demonstrate that individual adaptability mediates the relationship between PI and psychological well-being in the context of small enterprise employees of Uganda, an African developing country.